Question
upstudy study bank question image url

Find the derivative of the function \( G(x)=\left(1+\left(7+2 x^{8}\right)^{4}\right)^{6} \)

Ask by Morrison Zimmerman. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( G(x) \) is \( G'(x) = 384x^7(7 + 2x^8)^3[1 + (7 + 2x^8)^4]^5 \).

Solution

We start with the function   G(x) = [1 + (7 + 2x⁸)⁴]⁶. To differentiate G(x), we use the chain rule. Notice that G(x) is a composite function where the outer function is   F(u) = u⁶  with u = 1 + (7 + 2x⁸)⁴. Step 1. Differentiate the outer function with respect to u:   F'(u) = 6u⁵. So the derivative involving u becomes:   dG/dx = 6[1 + (7 + 2x⁸)⁴]⁵ · (du/dx). Step 2. Now differentiate the inner function u = 1 + (7 + 2x⁸)⁴. Note that the constant 1 differentiates to 0, so differentiate just (7 + 2x⁸)⁴. Let   v(x) = 7 + 2x⁸. Then u = 1 + [v(x)]⁴, and using the chain rule again:   d/dx [v(x)]⁴ = 4[v(x)]³ · v'(x). Now, differentiate v(x):   v(x) = 7 + 2x⁸  ⟹  v'(x) = 0 + 16x⁷ = 16x⁷. Thus,   du/dx = 4(7 + 2x⁸)³ · 16x⁷ = 64x⁷(7 + 2x⁸)³. Step 3. Combine the results:   G'(x) = 6[1 + (7 + 2x⁸)⁴]⁵ · 64x⁷(7 + 2x⁸)³. Multiply the constants:   6 · 64 = 384. So the final derivative is:   G'(x) = 384x⁷(7 + 2x⁸)³[1 + (7 + 2x⁸)⁴]⁵.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the derivative of the function \( G(x)=\left(1+\left(7+2 x^{8}\right)^{4}\right)^{6} \), we will use the chain rule multiple times. 1. Start by letting \( u = 1 + (7 + 2x^8)^4 \). Thus, \( G(x) = u^6 \). 2. Next, we find the derivative of \( G(x) \) with respect to \( u \): \[ \frac{dG}{du} = 6u^5. \] 3. Now we need to find the derivative of \( u \) with respect to \( x \): \[ u = 1 + (7 + 2x^8)^4. \] Let \( v = 7 + 2x^8 \). Thus, \( u = 1 + v^4 \). 4. Find \( \frac{du}{dv} \): \[ \frac{du}{dv} = 4v^3. \] 5. Now we find \( \frac{dv}{dx} \): \[ v = 7 + 2x^8 \implies \frac{dv}{dx} = 16x^7. \] 6. Combining these using the chain rule: \[ \frac{du}{dx} = \frac{du}{dv} \cdot \frac{dv}{dx} = 4v^3 \cdot 16x^7 = 64v^3 x^7. \] 7. Finally, we find \( \frac{dG}{dx} \) using the chain rule: \[ \frac{dG}{dx} = \frac{dG}{du} \cdot \frac{du}{dx} = 6u^5 \cdot 64v^3 x^7. \] Now substituting \( u \) and \( v \): \[ \frac{dG}{dx} = 6(1 + (7 + 2x^8)^4)^5 \cdot 64(7 + 2x^8)^3 x^7. \] This can be simplified: \[ \frac{dG}{dx} = 384(1 + (7 + 2x^8)^4)^5 (7 + 2x^8)^3 x^7. \] And that's the derivative of the function \( G(x) \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy